Przygody z klasyką? "Rewizor" Mikołaja Gogola w interpretacji Łukasza Czuja - Gracla, Jadwiga (Rusycystyczne Studia Literaturoznawcze, 2015)
The subject matter of the present analysis is Łukasz Czuj’s production titled “The Government Inspector”. The authoress juxtaposes the original text with the aforementioned interpretation, and points to numerous discrepancies. The divergences noticeable in Czuj’s production, such as different space arrangement, shift of focus, change in the genre, may result from the director’s fascination with the Russian culture of the 20s and 30s. However, the divergences are not motivated by the text of the drama, which leads to the conclusion that Czuj’s version, though admittedly interesting, is unfortunately inconsistent with the assumptions of the text.